Redox-inactive ions control the redox-activity of molecular vanadium oxides. Issue 17 (21st April 2020) - Greiner, Simon; Schwarz, Benjamin; Ringenberg, Mark; Dürr, Maximilian; Ivanovic-Burmazovic, Ivana; Fichtner, Maximilian; Anjass, Montaha; Streb, Carsten
Abstract : The enhanced redox-activity of a molecular vanadium oxide cluster upon functionalization with redox-inert Ca 2+ ions is reported together with initial insights into its performance as a lithium ion battery cathode. Abstract : Polyoxometalates are key materials for energy conversion and storage due to their unique chemical tunability and electrochemical reactivity. Herein, we report that functionalization of molecular vanadium oxides, polyoxovanadates, with redox-inert Ca 2+ cations leads to a significant increase in their electron storage capabilities. The electrochemical performance of the Ca 2+ -functionalized dodecavanadate [Ca2 V12 O32 Cl(DMF)3 ] 2− (=Ca 2 V 12 ) was thus compared with that of the precursor compound (H2 NMe2 )2 [V12 O32 Cl] 3− (=V 12 ). Ca 2 V 12 can store up to five electrons per cluster, while V 12 only shows one reversible redox transition. In initial studies, we demonstrated that Ca 2 V 12 can be used as an active material in lithium-ion cathodes. Our results show how redox-inert cations can be used as structural and electrostatic stabilizers, leading to major changes in the redox-chemistry of polyoxovanadates.